The Effects of Cooperative Learning Using CIRC Technique with Game Applications on Analytical Reading, Reading Comprehension Abilities in Thai Language, and Satisfaction of Grade 3 Students - Artwichaipawara, Sasineth; Phungphet, Siriporn (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were: 1) to compare the analytical reading and reading comprehension abilities in the Thai language of Grade 3 students before and after participating in cooperative learning activities using the CIRC technique combined with game applications; 2) to compare the students' reading comprehension abilities after the lessons using the CIRC technique with the 70% criterion; and 3) to study the satisfaction level of Grade 3 students towards the cooperative learning activities using the CIRC technique with game applications. The sample consisted of 25 Grade 3 students selected through cluster random sampling. The research instruments included four learning management plans totaling 16 hours, and the Thai language reading and comprehension test comprised 15 multiple-choice questions. analyzed using percentages, means, standard deviations, and one-sample t-tests. The research results were as follows: 1) The analytical reading and reading comprehension abilities of Grade 3 students after participating in cooperative learning activities using the CIRC technique with game applications were statistically significantly higher than before, at the 0.05 level. 2) The reading comprehension abilities of Grade 3 students after participating in cooperative learning activities using the CIRC technique with game applications reached 96%, statistically significantly higher than the 70% criterion at the 0.05 level. 3) The satisfaction level of Grade 3 students towards the cooperative learning activities using the CIRC technique with game applications was at the highest level.